The Effectiveness of a Realistic Mathematics Education to Increase Higher Order Thinking Skill (HOTS) of Secondary School Students - Muhammad Ammar Naufal; Ibrahim Abdullah Alshaye (Universitas Negeri Makassar, 2023)
This study aims to determine the effectiveness of using a realistic mathematical approach to the Higher Order Thinking Skill (HOTS) of SMA Negeri 2 Majene (SMAN 2 Majene), Indonesia. The subjects of this research were four students of class XI at SMAN 2 Majene. This research used a descriptive qualitative method. The instrument used was PISA-based HOTS questions developed based on a realistic mathematical approach to test students' HOTS. The average score obtained by students in answering test questions ranged from 61-80. It was concluded that the HOTS of SMA Negeri 2 Majene students were good. It showed that the realistic mathematics education effectively increased students' HOTS.